Added-value of texture analysis of ADC in predicting the survival of patients with 2018 FIGO stage IIICr cervical cancer treated by concurrent chemoradiotherapy. Issue 150 (May 2022) - Zhang, Xiaomiao; Zhang, Qi; Guo, Jinxia; Zhao, Jingwei; Xie, Lizhi; Zhang, Jieying; An, Jusheng; Yu, Xiaoduo; Zhao, Xinming
Highlights: Texture analysis of the ADC maps could provide effective information in predicting the outcomes of stage IIICr CSCC patients treated by CCRT. ADC maps could be used along with clinical prognostic biomarkers to predict PFS and OS in patients with stage IIICr CSCC treated by CCRT. Compared with the 2018 FIGO staging system, the combined model could significantly improve the prediction performance, as well as be used to identify high-risk patients. Abstract: Purpose: To investigate the value of texture analysis of ADC in predicting the survival of patients with 2018 International Federation of Gynecology and Obstetrics (FIGO) stage IIICr cervical squamous cell cancer (CSCC) treated with concurrent chemoradiotherapy (CCRT). Methods: A total of 91 patients with stage IIICr CSCC treated by CCRT between January 2014 and December 2018 were retrospectively enrolled in this study. Clinical variables and 21 first-order texture features extracted from ADC maps were collected. Univariate and multivariate Cox hazard regression analyses were performed to evaluate these parameters in predicting progression-free survival (PFS) and overall survival (OS). The independent variables were combined to build a prediction model and compared with the 2018 FIGO staging system. Survival curves were generated using the Kaplan-Meier method, and the log-rank test was used for comparison. Results: Mean Absolute Deviation (MAD), T stage, and the number of lymph node metastasis (LNM) were independently associated with PFS, while MAD, energy, T stage, number of LNM, and tumor grade were independently associated with OS. The C-index values of the combined models for PFS and OS, which were respectively 0.750 and 0.832, were significantly higher compared to 2018 FIGO staging system values of 0.629 and 0.630, respectively (P < 0.05). Conclusions: The texture analysis of the ADC maps could be used along with clinical prognostic biomarkers to predict PFS and OS in patients with stage IIICr CSCC treated by CCRT.